Utilização de poliacrilamidas de alto peso molecular na flotação catiônica reversa de minério de ferro - Henrique Dias Gatti Turrer (2004)
Flotation is an important iron ores concentration process. A major problem occurring in the concentrators is the low metallurgical recovery associated mainly with the fine size fraction. In this work, the utilization of synthetic flocculant utilization in the iron ore cationic reverse flotation was investigated. The flocculants used were high molecular weight polyacrylamides of different ionic grades. Flotation tests were performed to compare the results in the presence and absence of polyacrylamide. Sedimentation tests allowed to conclude that flocs formed by low polyacrylamides dosages are similar to those formed by starch solution. Further, it was verified that polyacrylamides do not prevent starch adsorption. It was observed that cationic and non ionic polyacrylamides cause a significant raise in the process metallurgical recovery. On the other hand, the anionic polyacrylamides did not improve the flotation performance. This metallurgical recovery increase was accompanied by a slight decrease in the quality of the concentrate. The flotation in the presence of polyacrylamides was strongly influenced by the pulp hydrodynamic conditions, such as speed and weight percent solids in the conditioning and flotation stages